PENERAPAN SUPERVISI KLINIS UNTUK MENINGKATKAN KINERJA GURU PADA ASPEK PEDAGOGI DALAM MENGEMBANGKAN RPP DI SMAN 5 BUNGO - agus wiyanta (LP3M STKIP Muhammadiyah Muara Bungo, 2022)
This study aims to improve the performance of teachers in pedagogical aspects in developing lesson plans (RPP) through clinical supervision. This research is a school action research (PTS) conducted with four stages, namely planning, implementation, observation and reflection. The subjects of this study were teachers of class X MIPA, X IPS, XI MIPA, XI IPS, XII MIPA and XII IPS at SMAN 5 Bungo. Data collection techniques were carried out by direct observation of teacher competence in developing lesson plans. The success of PTS can be seen from the increase in performance from an average score of 72.1% in the first cycle in the good category to 86% in the second cycle in the very good category. So it can be concluded that the application of clinical supervision can improve teacher performance in the pedagogical aspect in developing lesson plans